Disease burden from foodborne illnesses in Taiwan, 2012–2015 - Ying-Ho Lai; Yu-An Chung; Yun-Chun Wu; Chi-Tai Fang; Pei-Jer Chen (Journal of the Formosan Medical Association, 2020)
Background/Purpose: Foodborne disease is a global health problem. We aim to provide the first national estimate on disease burden from foodborne illnesses in Taiwan. Methods: We adopted the World Health Organization (WHO) Foodborne Disease Burden Epidemiology Reference Group (FERG) methodology framework, and used a hazard-based incidence approach to calculate disability-adjusted life year (DALY) lost to foodborne diseases. Estimated annual incidences and associated medical costs are based on the National Health Insurance research database. We redistributed incidence of unspecified acute gastroenteritis to specific foodborne pathogens, using reported bacteria, virus, parasite survey results in such cases as the reference. The percentage of foodborne illnesses not seeking medical attention is based on data reported from a nationwide survey. Results: During 2012–2015, 3,895,914 (90% confidence interval [CI]: 3,493,530–4,442,690) foodborne illnesses (1,445,384 sought medical care, with 50 deaths) occurred annually, which caused a total loss of 4974 (90%CI: 4671–5367) DALYs in Taiwan. The annual medical cost was NT$1.3 billion. Young (<5 years) children had the highest incidence. Among the 53% of foodborne illnesses cases with identifiable causal microorganisms, non-typhoid Salmonella, norovirus, and Vibrio parahaemolyticus were leading pathogens (annual foodborne incidence: 185,977, 157,656, and 99,351, respectively). Cases caused by non-typhoid Salmonella peaked in summer, while that caused by norovirus peaked in winter. Conclusion: Foodborne illnesses cause a substantial disease burden in Taiwan. Establishment of active surveillance and investigation mechanisms for the leading foodborne pathogens is warranted.